Transcriptomic Analysis of the Brucella melitensis Rev.1 Vaccine Strain in an Acidic Environment: Insights Into Virulence Attenuation - Salmon-Divon, Mali; Zahavi, Tamar; Kornspan, David (Frontiers in Microbiology, 2019)
The live attenuated Brucella melitensis Rev.1 (Elberg-originated) vaccine strain is widely used to control the zoonotic infection brucellosis in small ruminants, but the molecular mechanisms underlying the attenuation of this strain have not been fully characterized. Following their uptake by the host cell, Brucella replicate inside a membrane-bound compartment—the Brucella-containing vacuole—whose acidification is essential for the survival of the pathogen. Therefore, identifying the genes that contribute to the survival of Brucella in acidic environments will greatly assist our understanding of its molecular pathogenic mechanisms and of the attenuated virulence of the Rev.1 strain. Here, we conducted a comprehensive comparative transcriptome analysis of the Rev.1 vaccine strain against the virulent reference strain 16M in cultures grown under either normal or acidic conditions. We found 403 genes that respond differently to acidic conditions in the two strains (FDR < 0.05, fold change ≥ 2). These genes are involved in crucial cellular processes, including metabolic, biosynthetic, and transport processes. Among the highly enriched genes that were downregulated in Rev.1 under acidic conditions were acetyl-CoA synthetase, aldehyde dehydrogenase, cell division proteins, a cold-shock protein, GroEL, and VirB3. The downregulation of these genes may explain the attenuated virulence of Rev.1 and provide new insights into the virulence mechanisms of Brucella.